An insight on needs analysis towards the development of animated infographic module in Arabic grammar learning - Abdul Hamid, Mohd Fauzi; Ab. Halim, Zulazhan; Sahrir, Muhammad Sabri (Selcuk University, 2020)
Arabic grammar learning - which uses textbooks with lengthy details can be translated into creative and innovative forms through the application of technology advancement. Animated infographics is one of the many technological applications aimed to innovate learning information or content into simple, interesting, and easy to understand materials. This study gathered students’ perspectives in relation to their needs on form - hence, developing a module for animated infographics in Arabic grammar learning. This research employed Design and Development Research (DDR) methodology and approaches. It involved need analysis data where the first phase used a questionnaire on the use of learning material, issues regarding learning approaches, tendencies to use innovation, and needs of using animated infographics. The questionnaires were distributed conveniently to 248 undergraduate students studying Bachelor of Arabic Language Studies, who took a course entitled ‘Ibn Aqil’ Syntatical Texts. Quantitative data was then analyzed using Statistical Package for Social Science (SPSS) application to retrieve percentage, mean and standard deviations. Findings revealed a high need to develop a module for animated infographics in the Arabic grammar learning based on students’ opinions after taking the course. Innovative technological application on the syllabus of textbook learning, particularly the complex Arabic grammar was much needed in order to enable comprehension and provide focus.